Depressive Symptoms and Involvement in Physical Fighting among Portuguese Adolescents - Fraga, S (2017)
In this article, authors present findings on the relationship between depressive symptoms and involvement in physical fighting in late adolescence. Participants were 1,380 Portuguese adolescents initially recruited in 2003 to the EPITeen cohort. Depressive symptoms were assessed at 13 and 17 years of age using Beck Depressive Inventory II (BDI). Physical fighting was recorded at the age of 17. For girls, there was a significant association between depressive symptoms and physical fighting for those who scored BDI >13 at 17 years old and remained statistically significant after adjustment. For boys, those who scored >13 in both study waves presented higher crude odds to engage in fights that were attenuated after adjusting for grade retention. Depressive symptoms were significantly related to physical fighting involvement during adolescence, for both genders. However, whereas for female adolescents the association was significant when relevant symptoms and fighting occurred in the same period, for male adolescents such symptoms must have persisted from 13 to 17 years of age.